Effects of Antiretroviral Therapy on the Survival of Human Immunodeficiency Virus-positive Adult Patients in Andhra Pradesh, India: A Retrospective Cohort Study, 2007-2013 - Ram Bajpai; Himanshu Chaturvedi; Lakshmanan Jayaseelan; Pauline Harvey; Nicole Seguy; Laxmikant Chavan; Pinnamaneni Raj; Arvind Pandey (Korean Society for Preventive Medicine, 2016)
Objectives The survival outcomes of antiretroviral treatment (ART) programs have not been systematically evaluated at the state level in India. This retrospective study assessed the survival rates and factors associated with survival among adult human immunodeficiency virus (HIV)-infected patients in Andhra Pradesh, India. Methods The present study used data from 139 679 HIV patients aged ≥15 years on ART who were registered from 2007 to 2011 and were followed up through December 2013. The primary end point was death of the patient. Mortality densities (per 1000 person-years) were calculated. Kaplan-Meier and Cox-regression models were used to estimate survival and explore the factors associated with survival. Results The overall median follow-up time was 16.0 months (2.0 months for the deceased and 14.0 months for those lost to follow-up). Approximately 13.2% of those newly initiated on ART died during follow-up. Of those deaths, 56% occurred in the first three months. The crude mortality rate was 80.9 per 1000 person-years at risk. The CD4 count (adjusted hazard ratio [aHR],4.88; 95% confidence interval [CI], 4.36 to 5.46 for <100 cells/mm3 vs. >350 cells/mm3), functional status (aHR, 3.05; 95% CI, 2.82 to 3.30 for bedridden vs. normal), and body weight (aHR, 3.69; 95% CI, 3.42 to 3.97 for <45 kg vs. >60 kg) were strongly associated with the survival of HIV patients. Conclusions The study findings revealed that high mortality was observed within the first three months of ART initiation. Patients with poor baseline clinical characteristics had a higher risk of mortality. Expanded testing and counseling should be encouraged, with the goal of ensuring early enrollment into the program followed by the initiation of ART in HIV-infected patients.